(untitled) (International journal of medical sciences, 2026)
Thyroid cancer (TCC) is endocrine glands the widest widespread dangerous growth cancer of the disease general 1-1.5% in its composition does. Last in years of thyroid cancer stable growth, especially young and middle years old among screening programs, as well as a single diagnostic tactic absence this the problem world of oncology current problems in line introduces [6]. Literature information analysis that shows that QB S diagnostics one row serious related to difficulties. On the one hand, to the clinic was in phase Osmani traditional determination by methods often difficult, some in cases and possible not. Other side, thyroid of the gland wide widespread in the form’s tumor of the process real duration and his/her neck around with members​ attitude always exactly by designating does not happen [12].